(In)visibilidades da violência e do preconceito em Cidade de Deus e Minha alma : representações e identidades do homem negro brasileiro - Rostey, João Carlos Mayer (2009)
This research, linked to Grupo de Estudos em Análise do Discurso (Study Group of Discourse Analysis) of Universidade Estadual de Maringá (State University of Maringá) - GEDUEM, approaches the constitution of identity and the representation of black man from the ghetto. From this point of view, the identities are understood as a process and discursive effect which involve the contemporary mediatic discursive practices, established by relations of knowledge and power. It is through of these relations that disciplinary devices are operated in search of the domain over the bodies in sociopolitical, economic and cultural field of a society, by positioning the subject and establishing when and what place he/she must occupy in this process. The reflections and the studies carried out in this thesis which offered support to the interpretative-descriptive and archaeological and genealogical movement were stimulated by the following questions: in contemporary national mediatic discursive practices, the representation of Brazilian black man occurs in a discrimination's relation with non-black? Such relation can be identified in the cinematographic production Cidade de Deus (City of God), by Fernando Meireles, and in the videographic production Minha Alma (My Soul), by the group O Rappa? Thinking about these questions, our hypothesis is that the media constitute a place of politic conflict when it put in circulation discourses about the Brazilian black man from the ghetto in contradiction to the constitutive memory concerning to the idea that we live in a "racial democracy"in this country. As a theoretical and methodological movement, our attempt of description and interpretation are based on the Discourse Analysis' concepts (FOUCAULT, 1962, 1986), such as enunciation, enunciative function, discursive practice, discursive formation, file, ways of subjectivation, memory (HALBAWACHS, 2004; COURTINE, 2006) and history; on the studies about image, representation, (in)visibility, on the relation between real and reality (AUMONT, 1993; MANGUEL, 1997; DUBOIS, 2004) as well on the articulations about identity (HALL, 2000, 2003). In the aesthetic field, the reflections dialogue with the following movements: "Estética da Fome" (Aesthetics of Starvation) and "Cosmética da Fome" (Cosmetics of Starvation), both political and sociocultural. To reach this purpose, it was taken as reference the considerations elaborated by Rocha (1965) and Bentes (2005). Under such theoretical and analytical principles, we established as main objective the determination of how the cinematographic and television's media portraits the Brazilian black man from Rio de Janeiro's ghetto in the movie Cidade de Deus (City of God) and in the video clip Minha Alma (My Soul). To achieve this end, we will observe how the imagetic discourses, with their mechanisms such as frameworks, plans, focus etc., produce sayings and nonsayings in the opacity of their constitution. Delineated like this, the expectation created with the development of this research is that it can contribute with reflections and discussions about its theme and implications (the racial discrimination and the public politics of inclusion in/by media), as well about the possibilities of thematic approaches in interlinked fields (linguistics, politics and aesthetics). In interfaces of different languages, in confluence of history and discursive memory, the results obtained by the development of this research indicate that it is established a relation of strength or resistance of collective imaginary about the Brazilian black man from Rio de Janeiro's ghetto through the media analyzed.